Outcome of patients with streptococcal prosthetic joint infections with special reference to rifampicin combinations. Issue 1 (December 2016) - Fiaux, E.; Titecat, M.; Robineau, O.; Lora-Tamayo, J.; El Samad, Y.; Etienne, M.; Frebourg, N.; Blondiaux, N.; Brunschweiler, B.; Dujardin, F.; Beltrand, E.; Loiez, C.; et al.
Abstract Background Outcome of patients with streptococcal prosthetic joint infections (PJIs) is not well known. Methods We performed a retrospective multicenter cohort study that involved patients with total hip/knee prosthetic joint (THP/TKP) infections due toStreptococcus spp. from 2001 through 2009. Results Ninety-five streptococcal PJI episodes (50 THP and 45 TKP) in 87 patients of mean age 69.1 ± 13.7 years met the inclusion criteria. In all, 55 out of 95 cases (57.9 %) were treated with debridement and retention of the infected implants with antibiotic therapy (DAIR). Rifampicin-combinations, including with levofloxacin, were used in 52 (54.7 %) and 28 (29.5 %) cases, respectively. After a mean follow-up period of 895 days (IQR: 395–1649), the remission rate was 70.5 % (67/95). Patients with PJIs due toS. agalactiae failed in the same proportion as in the other patients (10/37 (27.1 %) versus 19/58 (32.7 %);p = .55). In the univariate analysis, antibiotic monotherapy, DAIR, antibiotic treatments other than rifampicin-combinations, and TKP were all associated with a worse outcome. The only independent variable significantly associated with the patients' outcomes was the location of the prosthesis (i.e., hip versus knee) (OR = 0.19; 95 % CI 0.04–0.93;p value 0.04). Conclusions The prognosis of streptococcal PJIs may not be as good as previously reported, especially for patients with an infected total knee arthroplasty. Rifampicin combinations, especially with levofloxacin, appear to be suitable antibiotic regimens for these patients.